Endoscopic Transorbital Approach for Select Recurrent and Newly Diagnosed Anteromedial Temporal Lobe Gliomas - Tangsrivimol, Jonathan A.; Delavari, Nader; Godfrey, Kyle J.; Schwartz, Theodore H. (Journal of Neurological Surgery Part B: Skull Base, 2025)
The endoscopic lateral transorbital approach (eLTOA) has emerged as a minimal access technique for accessing the middle fossa and periorbital region. This study explores the applicability of eLTOA in the management of recurrent and newly diagnosed medial temporal lobe gliomas.Forty patients at our institution underwent eLTOA between 2016 and 2024. There were five surgeries for glioma. Patients were assessed for demographic and clinical data, radiographic characteristics, and histopathological and molecular findings.Four recurrent gliomas required biopsy for diagnosis and molecular genotyping, and one newly diagnosed tumor aimed for gross total resection (GTR). Histologic diagnoses remained unchanged in three recurrent cases (two glioblastoma multiforme and one xanthoastrocytoma). One case was upgraded from oligoastrocytoma Grade II to glioblastoma Grade IV. GTR was achieved in the newly diagnosed tumor, with histology confirming dysembryoplastic neuroepithelial tumor. Average length of stay was 3 days. There was one case of transient diplopia.eLTOA offers a minimally invasive, direct approach to medial temporal lobe gliomas that minimizes the risks of infection and temporalis muscle atrophy associated with reoperation through a previously irradiated incision. It is most useful for restaging recurrent tumors, although GTR can be obtained in well-selected newly diagnosed tumors.
Keywords: glioma; transorbital; endoscopic; temporal lobe; low grade; high grade